Perception of the law on the example of agricultural land consolidation - Truszkiewicz, Zygmunt (Przegląd Prawa Rolnego, 2024)
The perception of the nature and role of the law has a fundamental influence on its impact on social relations of legal significance. It also translates into a greater or lesser activity of the bodies applying the law. In countries with legal systems categorised as civil law, the image of the law is shaped mainly by doctrine and to a lesser extent by judicature, contrary to the common law countries where the law is “judge-made” and mainly based on judicial decisions. This different perception of the law is of practical significance as it does not remain without influence on the mechanisms by which the law operates. Looking at the law through the prism of the circumstances of a particular case, especially one classified as a hard case, allows us to see the nature of the law in a sharper way, including the relationship between the concretisation of the content of legal norms and socio-economic and political conditions. A case of great social importance and at the same time of legal complexity is a consolidation proceeding, especially one that lasts for decades. In the context of such cases it is clear that regulations cannot be equated with law but may only constitute a starting point for the search for appropriate legal norms necessary for the adjudication of specific cases. Hence the potentially momentous role, in this dimension, of the body that will apply the law with the objective of concretising just and equitable legal norms.